Magic Paper Becomes Teacher: Revolutionary Pop-Up Book for Learning Mathematics in Grade IV of SD 38 Janna-Jannaya - Lisdayanti, A.; Paronda, Naimah; Asfar, Andi Muhammad Irfan Taufan (Unram Journal of Community Service, 2025)
Mathematics is often seen as a difficult subject by elementary school students, especially because it is abstract and less interesting. In this article, we will discuss the implementation innovative learning media in the from of a pop-up book entitled “Magic Paper to Become a Teacher” in class IV at SD 38 Janna-Jannaya. The is to improve students’ understanding of mathematical concepts. This activy was carried out in two stages: first, the pop-up book was  introduced, and second, it increased students’ direct internation with the visual and mechanical elements of the book. The results obtained show an increase in students’ understanding and interest, create a more interactive learning atmosphere, and show more satisfactory evaluation results compared to conventional methods. Even though there are several obstacles, such as limited time and the number of books available, the use on this media has proven to be effective in creating a fun and meaningfull learning experience. Thus, pop-up books have great innovative solution that can be widely applited increasing the effectiveness of mathematics learning for elementary school students